Validation of Road Load Characteristic of a Sub-Compact Vehicle by Engine Operation - D., Ramasamy; Goh, Chin Yuan; R. A., Bakar; Z. A., Zainal (Universiti Malaysia Pahang, 2014)
Vehicle efficiency relates to pollutants and cost savings in third world countries. In term of subcompact cars, the vehicle characteristics are governed by the engine and road load characteristics. Overall, it involves the rolling resistance and aerodynamics loading on the moving car on the road. Tests were conducted on a local subcompact car to measure engine speed, throttle position and air fuel ratio while Global Positioning Systems (GPS) recorded data of the vehicle speed and position. Also, dynamometer testing was done to reflect the vehicle characteristics. The results of on the road roll down test and cruising test were combined to get the road load characteristics of the vehicle. A comparison of the road loads obtained with actual engine dynamometer test was found to have about 5% error. The errors of the experiments shows the validation of the tests.